PENGARUH JUS LABU SIAM TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DENGAN PREEKLAMSIA - Nasution, Naimah; Insani, Septa Dwi; Hayati, Erlina; Lumban Raja, Reti (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Hypertensive pregnancy is a major contributor to high maternal mortality and can negatively impact pregnancy and childbirth. One non-pharmacological therapy with minimal side effects that pregnant women with hypertension can consume is chayote. Chayote is a vegetable that can prevent hypertension and lower cholesterol. It is a good source of nutrition for pregnant and breastfeeding women. This study aimed to determine the effect of administering chayote to pregnant women with hypertension. The research design used was Quasi Experiment (quasi experiment) by using Pretest - Posttest One Group Design. Data collection was carried out in May 2025. The population was pregnant women with hypertension who checked themselves at the Sumiariani Clinic in March – May 2025, namely 20 mothers. The sampling technique used in this research is Total Sampling.The average systole of pregnant women before giving Chayote Juice was 163.65 and the average diastole was 104.55. The average systole of pregnant women after giving Chayote Juice was 154.55 and the average diastole was 95.35, with a p-value of 0,000<0,005 which means that there is an effect of giving chayote juice to pregnant women with preeclampsia. Its is hoped that the Sumiariani Clinic can provide education to pregnant women with preeclampsia regarding the effects of chayote juice on lowering their blood pressure.